Surgical Therapy After Failed Feminizing Genitoplasty in Young Adults with Disorders of Sex Development: Retrospective Analysis and Review of the Literature. Issue 10 (18th August 2021) - Ellerkamp, Verena; Rall, Kristin Katharina; Schaefer, Juergen; Stefanescu, Diana; Schoeller, Dorit; Brucker, Sara; Fuchs, Joerg
ABSTRACT: Background: Secondary vaginal stenosis may occur after reconstruction of genital malformations in childhood or after failed vaginal aplasia repair in adults. Aim: This study focusses on the results of the surgical treatment of these patients in our multidisciplinary transitional disorders/differences of sex development team of pediatric surgeons and gynecologists. Methods: A retrospective analysis was carried out on adult and female identified disorders/differences of sex development patients with vaginal stenoses treated between 2015 and 2018 in a single center with revision vaginoplasty. The underlying type of malformation, the number and surgical techniques of vaginoplasties in infancy, techniques of revision of the stenotic vagina, vaginal length and caliber, possibility of sexual intercourse, and temporary vaginal dilatation. A review of literature with regard to recommended surgical techniques of revision vaginoplasties was accomplished. Outcomes: To describe the surgical technique, the main outcome measures of this study are vaginal calipers after revision vaginoplasty as well as ability for sexual intercourse. RESULTS: Thirteen patients presented with vaginal stenosis with a median age of 19 years (range 16–31). All patients had one or more different types of vaginoplasties in their medical history, with a median age at first vaginoplasty of 15 months (0–233). Underlying anatomical conditions were urogenital sinus (n = 8), vaginal agenesis (n = 2), persistent cloacae (n = 2), and cloacal exstrophy (n = 1). The main symptoms were disability of sexual intercourse in 13 patients due to stenotic vaginal tissue. The most frequently performed surgical technique was partial urogenital mobilization with a perineal or lateral flaps (n = 10), followed by bowel vaginoplasty (n = 2), in 1 patient a revision vaginoplasty failed due to special anatomical conditions. In a median follow-up of 11 months, all but one patient presented with physiological vaginal length and width, and normal sexual intercourse in those with a partnership. Clinical Implications: Perineal flap with partial urogenital mobilization should be considered as a treatment of choice in severe cases of distal vaginal stenosis and after multiple failed former vaginoplasties, while bowel vaginoplasty should be reserved only for cases of complete cicatrization or high located stenosis of the vagina. Strengths & Limitations: The strength of this study is the detailed description of several cases while the retrospective character is a limitation. CONCLUSION: In patients after feminizing genital repair, perineal flap with partial urogenital mobilization provides a normal anatomical outcome and allows unproblematic sexual intercourse.